2010
DOI: 10.1111/j.1600-6143.2010.03212.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a Novel Efalizumab‐Based Immunosuppressive Regimen to Facilitate Single Donor Islet Cell Transplantation

Abstract: Islet transplantation is an experimental therapy for selected patients with type 1-diabetes (T1DM). It remains limited by immunosuppressive drug toxicity, progressive loss of insulin independence, allosensitization, and the need for multiple islet donors. We describe our experience with an efalizumab-based immunosuppressive regimen as compared to the prevailing standard regimen, the Edmonton protocol. Twelve patients with T1DM received islet transplants: 8 were treated with the Edmonton protocol; 4 were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 21 publications
1
90
0
3
Order By: Relevance
“…In one trial, all 8 patients who received an islet transplant and were treated with an Efalizumab-based regimen achieved insulin independence; 4 of these patients achieved independence after a single islet transplant (Posselt et al, 2010). In the second study, the 4 patients that were treated with an Efalizumab based regimen achieved insulin independence after a single islet transplant (Turgeon et al, 2010). Efalizumab was ultimately removed from the market in 2009 due to 4 cases of progressive multifocal leukoencephalopathy (PML), however, none of the recipients in either of these studies demonstrated evidence of this disease (Posselt et al, 2010;Turgeon et al, 2010).…”
Section: Biologic Agents -Monoclonal Antibodies 311 Anti-lfa-1 Monomentioning
confidence: 99%
See 1 more Smart Citation
“…In one trial, all 8 patients who received an islet transplant and were treated with an Efalizumab-based regimen achieved insulin independence; 4 of these patients achieved independence after a single islet transplant (Posselt et al, 2010). In the second study, the 4 patients that were treated with an Efalizumab based regimen achieved insulin independence after a single islet transplant (Turgeon et al, 2010). Efalizumab was ultimately removed from the market in 2009 due to 4 cases of progressive multifocal leukoencephalopathy (PML), however, none of the recipients in either of these studies demonstrated evidence of this disease (Posselt et al, 2010;Turgeon et al, 2010).…”
Section: Biologic Agents -Monoclonal Antibodies 311 Anti-lfa-1 Monomentioning
confidence: 99%
“…Clinically, the humanized form, Efalizumab, has been used to treat another autoimmune disorder, plaque psoriasis, with few acute side effects (Lebwohl et al, 2003). There have been 2 trials to date in clinical islet allotransplantation that have reported its efficacy (Posselt et al, 2010;Turgeon et al, 2010). In one trial, all 8 patients who received an islet transplant and were treated with an Efalizumab-based regimen achieved insulin independence; 4 of these patients achieved independence after a single islet transplant (Posselt et al, 2010).…”
Section: Biologic Agents -Monoclonal Antibodies 311 Anti-lfa-1 Monomentioning
confidence: 99%
“…They represent plausible future directions in immunosuppression for allogeneic islet transplantation 44,45 . …”
Section: Evolution Of and Advancements In Immunosuppressive Protocolsmentioning
confidence: 99%
“…The islet-enriched proteins, namely glutamate decarboxylase-65, doublecortin, protein phosphatase 1, regulatory (inhibitor) subunit 1A (PPP1R1A), ubiquitin C-terminal hydrolase-L1 and the high-mobility group box-1 protein (HMGB1) were widely studied to predict the islet damage. However, the short half-life of these proteins restricts them to become reliable biomarker to predict the islet damage 45,[48][49][50] . In recent years, experiments on nucleic acid biomarkers such as miRNAs, circulating cell-free DNA (cfDNA), and unmethylated/methylated insulin DNA ratio have increased drastically.…”
Section: Biomarkers To Monitor Islet Graft Functionmentioning
confidence: 99%
“…Although graft and patient survival was excellent (95% and 97% at 6 months), there was an 11% rejection risk and an 8% PTLD incidence. Other groups have used efalizumab as adjunct therapy in islet transplant trials (Posselt et al 2010;Turgeon et al 2010) as part of a maintenance immunosuppression regimen. The use of this agent was halted because of an association with progressive multifocal leukoencephalopathy (PML), a serious and usually fatal central nervous system infection caused by JC polyoma virus (Carson et al 2009).…”
Section: Costimulatory Blockadementioning
confidence: 99%